Phytotherapy in cariology and restorative dentistry - de Souza Batista, Victor Eduardo [UNESP]; Catelan, Anderson; Vechiato-Filho, Aljomar José; Martins, Christine Men; Vasques, Ana Maria Veiga [UNESP]; Cury, Marina Tolomei Sandoval [UNESP]; Emerenciano Bueno, Carlos Roberto [UNESP] (My University, 2020)
The use of plant extract for health treatment has been reported over the years. The treatment of diseases that affect the oral cavity is not different, specifically for dental caries treatment. The American Academy of Cariology (AAC) defines the cariology as the science and art of understanding the etiology, mechanisms of the disease known as dental caries including initiation, reversal, progression, diagnosis, prognosis, risk management, prevention, non-surgical and surgical therapies, and oral health-focused outcomes. The use of herbal therapy is proposed in different stages of the mechanism of the dental caries disease, mainly in the diagnosis, prevention and treatment outcomes. This chapter will show the application of herbal therapy in the diagnosis and prevention as well as its application of herbal therapy regarding the treatment of the dental caries disease by restorative dentistry.
Keywords: Dental Caries; Dentistry; Ethnopharmacology; Operative; Phytotherapy